2021
DOI: 10.1002/pca.3093
|View full text |Cite
|
Sign up to set email alerts
|

Development of new and validated HPTLC methods for the qualitative and quantitative analysis of hyperforin, hypericin and hyperoside contents in Hypericum species

Abstract: Hypericum perforatum L. (St. John's wort) is a medicinally important member of Hypericaceae. Many pharmacological activities have been mostly attributed to its hyperforin, hypericin and/or hyperoside contents. Therefore, qualitative and quantitative determinations of these ingredients are essential to justify the beneficial effects of St. John's wort on health. In the European Pharmacopoeia, the TLC and HPLC methods were given for this purpose. High performance thin layer chromatography (HPTLC) has recently be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Typical constituents of Hypericum species essential oils include the monoterpenes α-and β-pinene (Figure 1), limonene and myrcene, the sesquiterpenes β-caryophyllene (Figure 1), and caryophyllene oxide, and hydrocarbons such as n-decane, C 16 -and C 29 alkanes and C 24 , C 26 and C 28 alkanols [3,4]. More specifically, flavonols (catechins), naphthodianthrons (hypericin, pseudohypericin), xanthones, coumarins, lycosides, anthraquinones, phloroglucinols (hyperforin, adhyperforin), flavonoids (rutin, hyperoside, quercitrin), flavonol glycosides, lactones, pyrones, lipids, triterpenes, and tannins represent the main constituents in H. perforatum [21]. Whereas, α-pinene, β-pinene, (E)-β-ocimene, β-caryophyllene and germacrene-D dominate constituents of H. helianthemoides, H. scabrum and H. perforatum from Iran [3].…”
Section: The Chemical Composition Of Essential Oils From Manymentioning
confidence: 99%
“…Typical constituents of Hypericum species essential oils include the monoterpenes α-and β-pinene (Figure 1), limonene and myrcene, the sesquiterpenes β-caryophyllene (Figure 1), and caryophyllene oxide, and hydrocarbons such as n-decane, C 16 -and C 29 alkanes and C 24 , C 26 and C 28 alkanols [3,4]. More specifically, flavonols (catechins), naphthodianthrons (hypericin, pseudohypericin), xanthones, coumarins, lycosides, anthraquinones, phloroglucinols (hyperforin, adhyperforin), flavonoids (rutin, hyperoside, quercitrin), flavonol glycosides, lactones, pyrones, lipids, triterpenes, and tannins represent the main constituents in H. perforatum [21]. Whereas, α-pinene, β-pinene, (E)-β-ocimene, β-caryophyllene and germacrene-D dominate constituents of H. helianthemoides, H. scabrum and H. perforatum from Iran [3].…”
Section: The Chemical Composition Of Essential Oils From Manymentioning
confidence: 99%
“…A recent study reported that Hyp contents obtained from Hypericum species can be analyzed quantitatively and qualitatively using high-performance thin-layer chromatography (HPTLC) methods [ 26 ]. However, the intact detection of Hyp using high-performance liquid chromatography-ultraviolet (HPLC-UV) or liquid chromatography-tandem mass spectrometry (LC-MS-MS) methods is nearly impossible because of the galactose sugar moiety of Hyp.…”
Section: Phytochemistry Of Hyperosidementioning
confidence: 99%
“…For complex sample analysis, hyphenated high-performance thin-layer chromatography (HPTLC) is a versatile tool that can be used for simultaneous sample separation, allowing authenticity screening [ 27 , 28 , 29 , 30 , 31 , 32 ], non-target bioprofiling [ 33 , 34 , 35 , 36 ], as well as quantification of chemical marker compounds [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] from a wide variety of samples, including foods, plants, and other natural products. The combination of multiple analytical steps and identification of bioactivity by the same workflow makes hyphenated HPTLC a very sustainable technique and allows complex mixtures, such as plant extracts, to be studied in parallel in a much faster and straightforward way [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%